Why python is a Good Programming Language for Learning to Program - Vasilјević, Nebojša (Infotheca - Journal for Digital Humanities; Vol 14 No 1 (2013): Infotheca - Journal of Informatics and Librarianship, 2024)
The choice of a programming language for learning to program highly depends on circumstances, so we can’t give a general answer which choice is the best, but there are programming languages that stand out with their characteristics as appropriate for learning to program. If you want to focus on understanding ideas and acquiring programming skills rather than mastering the programming language itself, and at the same time you want to choose a programming language that is well represented in practice, you can hardly make a better choice than Python.